+0  
 
0
238
1
avatar+389 

What does the fundamental theorem of algebra state about the equation 

 

 Mar 4, 2018
 #1
avatar+94526 
+1

2x^2   + 8x  + 14   =  0        divide through by 2

 

x^2  + 4x  +  7   =  0        subtract 7 ffrom both sides

 

x^2  +  4x  =  -  7         complete the square on x

 

x^2  + 4x  + 4  =  - 7  + 4

 

(x + 2)^2  =  - 3       take the root of both sides

 

x + 2  =   ±√-3

 

x + 2  =  ±√3 i

 

x  =  -2  ±√3 i  ⇒  First answer

 

 

cool cool cool

 Mar 4, 2018

6 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.